Release Kinetics of Boron in Acidic Soils as Affected by Calcium Form Different Sources - Roongnapa Bowichean; Richard William Bell; Miaomiao Cheng; Suphicha Thanachit; Somchai Anusontpornperm (Applied and Environmental Soil Science)
Boron (B) release mechanism is vital in supplying available B, particularly in acidic soils, because a temporary B deficiency can be triggered when liming the soil. This research was conducted with the aim at elucidating the role of Ca on B release kinetics in three acidic soils of Thailand to ascertain the kinetic release of B as affected by added calcium (Ca) from two sources: ground limestone (GL) and calcium chloride (CaCl2). Topsoil samples were incubated with either GL or CaCl2 at 0, 0.5, 1.0, or 1.5 times of the lime requirement for 7 days; thereafter, the soil pH and the kinetics of B release were analyzed based on successive extractions with 0.01 M CaCl2 solution for 72 h, which was comparatively described using four kinetic models: Elovich, parabolic diffusion, power function, and first-order of which each model would differently provide unique insights into the kinetic release of plant nutrient from soil. The added Ca significantly affected B release into the soil with the release kinetics of B in the two-time segments only conforming to the power function model in which approximately 70% of B was released rapidly during the initial phase and the rest was in a slow-release phase later on. Compared at the same rates of Ca applied, CaCl2 accelerated more B release than GL with no statistical difference in some soils. This was directly impacted by a decrease in soil pH as significantly caused by the addition of CaCl2. In addition, the B release rate significantly correlated with soil organic matter (r = 0.699∗∗, p<0.01). Our findings suggested that increasing soil organic matter should be recommended to provide more B availability but liming or using GL as a Ca source should be cautious as it can lead to B deficiency for plants grown in these acidic soils.